Transformation of the orator image (the Ethos ) at speech of AL- HASAN Ibn ALI Ibn ABI TALEB In Sabatt - Basal, Mohammed; Ahmed , Adnan; Fayad , Aksam (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The research attempts to compromise a linguistic case to be understand able it’s the theory in phase the formation, and it is the detection hangs in about the image which appeared in its personality of the oratorical self, the transformations which occurred on it, and their application mechanism to a linguistic text which is the speech of AL- HASAN Ibn ALI Ibn ABI TALEB In Sabatt. Moreover, The research attempts to set up a compromise that clarifies both sides of saying: theoretical and practical, so the research to importance indicated the rhetoric in describing its industry, and seeks to attracting the addresses "receivers" and the impacting and persuading them, and explain the components of the communication process, and illustrated the manifestations of the ethos, started with the advanced ethos that pertains to the person speaking, and through the oratorical ethos, it is the image that the speech producer tried to construct in the text, to reach the image of the self was formed after the end of the discourse, which proposed usher naming the post-rhetorical ethos, and how the recipient rebelled against the preacher when the third verb of the speech act was achieved. The analytical descriptive and method might sound the perfect way via which one can get to the speech of AL- HASAN Ibn ALI, analysis of procedural processes in the study of linguistic phenomena after determining their scope time and environment, and detecting shifts in the image of the discourse product "ethos" .